2021
DOI: 10.1002/ajb2.1766
|View full text |Cite
|
Sign up to set email alerts
|

Selfing rate variation within species is unrelated to life‐history traits or geographic range position

Abstract: Premise In plants, populations and species vary widely along the continuum from outcrossing to selfing. Life‐history traits and ecological circumstances influence among‐species variation in selfing rates, but their general role in explaining intraspecific variation is unknown. Using a database of plant species, we test whether life‐history traits, geographic range position, or abundance predict selfing rate variation among populations. Methods We identified species where selfing rates were estimated in at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…Species with multiple conflicting designations (i.e., studies indicating both SC and SI for the same species) were excluded. This decision was based on similar practices in other mating system studies (Moeller et al 2017, Prior and Busch 2021). These species with conflicting designations comprised 7.5% of the dataset.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Species with multiple conflicting designations (i.e., studies indicating both SC and SI for the same species) were excluded. This decision was based on similar practices in other mating system studies (Moeller et al 2017, Prior and Busch 2021). These species with conflicting designations comprised 7.5% of the dataset.…”
Section: Resultsmentioning
confidence: 99%
“…In keeping with previous studies (Goodwille et al 2005, Moeller et al 2017, papers which reported a sexual system (i.e., apomixis) but not a selfing designation were excluded. Sexual relatives of apomictic species are generally selfing, and apomixis has been hypothesized to be correlated with selfing (Hörandl 2009, Prior andBusch 2021), so this was unlikely to impact the inclusion of outcrossing species in the dataset. Additionally, crop species were excluded, as breeding efforts and crop domestication often directly select on the ability to self (Solís Montero et al 2021).…”
Section: Literature Review and Scopementioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has revealed that there is no general trend of selfing rate across populations of species when going from the central to the peripheral zones[26]. However, they did reveal that there was significant heterogeneity between species on this metric.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a shift in mating system towards self-compatibility and self-fertilization was described in the context of postglacial range expansion in Campanula americana 43 . Many hermaphroditic species may show such a trend, but detection is hampered by a lack of range-wide investigations on mating system variation 44 . Range expansions by serial bottlenecks were typical after Pleistocene glaciation cycles and may have often helped speciation.…”
Section: Discussionmentioning
confidence: 99%